Prognostic Significance of Blood Type A in Patients with Renal Cell Carcinoma - Ko, Kyungtae; Park, Young Hyun; Jeong, Chang Wook; Ku, Ja Hyeon; Kim, Hyeon Hoe; Kwak, Cheol (Urology Journal, 2016)
Purpose: In this study, we evaluated the prognostic significance of the ABO blood type in patients with renal cell carcinoma (RCC) who had undergone partial or radical nephrectomy. Materials and Methods: Information on the ABO blood type was obtained from 1750 patients with RCC. A total of 1243 men and 507 women (mean age, 55.41 ± 12.43 years) with RCC who had undergone partial or radical nephrectomy were enrolled in this study. The median follow-up duration was 35.0 months (interquartile range [IQR], 16.0-67.0). During the follow-up period, 271 patients experienced RCC recurrence, and 137 patients died from RCC. Results: Type A was the most common blood type (568, 32.5%), followed by type O (525, 30.0%), type B (464, 26.5%), and type AB (193, 11.0%). Generally, blood type was not associated with any clinicopathological factors. Unlike blood type O, the multivariate analysis of progression-free survival (PFS) showed that blood type non-O (A, B, and AB) was an independent prognostic factor for a worse outcome (95% confidence interval [CI]: 1.24- 2.37, hazard ratio [HR] = 1.71, P = .001; 95% CI: 1.08-2.13, HR = 1.51, P = .016; 95% CI: 1.03-2.43, HR = 1.58, P = .037, respectively). Cancer-specific survival (CSS) analysis showed that blood type A was an independent factor associated with a worse prognosis for CSS (95% CI: 1.05-2.64, HR 1.66, P = .031, respectively). Conclusion: The ABO blood type is significantly associated with PFS and CSS in patients with RCC following partial or radical nephrectomy. Blood type non-O (A, B, and AB) is an independent prognostic factor for a worse PFS outcome, and blood type A is an independent factor associated with a worse CSS prognosis.